CIL:41466, Sus scrofa domestica, epithelial cell. In Cell Image Library ... - Wadsworth, Patricia (UC San Diego Library Digital Collections, 2021)
Confocal image of a mitotic spindle in a dividing cell. The spindle is shown in yellow and the surrounding actin cytoskeleton is in blue. Images were acquired using a 100X NA 1.4 phase objective lens and a Perkin Elmer spinning disc confocal scan head. A Hammamatsu Orca ER cooled CCD camera was used to collect images. Image collection was driven using Metamorph software. Complete Z-series of images were collected and deconvolved using AutoQuant software. The image is a maximum intensity projection of a subset of the entire Z-stack; the same subset of the Z-stack is used in each channel. Sixth Prize, 2007 Olympus BioScapes Digital Imaging Competition. ... : Preparation: glutaraldehyde fixed tissue Relation to intact cell: dispersed cells in vitro Item type: recorded image Imaging mode: confocal microscopy Parameter imaged: fluorescence emission Source of contrast: distribution of epitope Visualization methods: phalloidin; primary antibody plus labeled secondary antibody; Fluorescein (FITC); Rhodamine Processing history: deconvolution; maximum projection ...